2022
DOI: 10.3390/medicina58040505
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Practices in Prevention of COVID-19 and Impacts among Population in Chiang Mai, Thailand

Abstract: Background and objectives: The pandemic of COVID-19 is a global concern requiring urgent and effective action. However, the data on prevention practices and the impact of COVID-19 among the Thai population have not been clearly described. This study aimed to examine the knowledge, attitudes, perception, practices, and factors predicting practices in the prevention of COVID-19 and to study the impact of COVID-19 on people’s livelihoods. Materials and Methods: A cross-sectional study was performed between April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The questionnaire on the effects of COVID-19 was developed by Kasatpibal et al [ 16 ], and validated in a Thai context. This questionnaire was a 16-item scale consisting of four subdimensions: (1) effects of health and disease prevention; (2) family effects; (3) economic effects; and (4) psychological components.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire on the effects of COVID-19 was developed by Kasatpibal et al [ 16 ], and validated in a Thai context. This questionnaire was a 16-item scale consisting of four subdimensions: (1) effects of health and disease prevention; (2) family effects; (3) economic effects; and (4) psychological components.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 A pilot study in Thailand demonstrated that the effects of the COVID-19 pandemic and government policies included a decrease in national travel (63.5%), eating out (63.0%), participation in religious, traditional and cultural activities (61.5%), patronage of beauty salons (61.0%), and shopping at the mall (58.0%). 8 A study in Zambia found that the spread of COVID-19 affected the education of students at the high school level. The teachers and students lacked support for online learning.…”
Section: Introductionmentioning
confidence: 99%
“…Some students reported a delay in graduation (61.0%), did not have devices and accessories needed for online learning (43.0%), had no support for solving problems during online learning (43.0%), had difficulty accessing or had no internet access for online learning (38.5%), and lacked the skills for online learning (38.0%). 8 The COVID-19 pandemic disrupted the global economy. It resulted in the economic slowdown of countries around the world, including Europe, the Americas, and Asia 10 resulting in a decrease of gross domestic product and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the effectiveness of teleconsultation to enhance self-care in cases of COVID-19 was challenging, however meeting the needs of the patients is a predominant task for the health care services. A recent study shows that Thai people have a high awareness of COVID-19 prevention; however, less than half (45.4%) have high levels of knowledge about COVID-19 [ 17 ]. The most common sources Thai people use to seek health information is from health care providers and media [ 18 ].…”
Section: Introductionmentioning
confidence: 99%